A TEN YEAR REVIEW OF EMERGENCY PERIPARTUM HYSTERECTOMY IN A TERTIARY CARE HOSPITAL - Khan, Bushra; Khan, Baynazir; Sultana, Ruqqia; Bashir, Rubina; Deeba, Farhat (Journal of Ayub Medical College Abbottabad, 2012)
Background: Emergency peripartum hysterectomy (EPH) is a life saving procedure considered in cases of severe haemorrhage unresponsive to medical and conservative surgical procedures. The aim of present study was to review the frequency, indications, maternal morbidity and mortality associated with emergency peripartum hysterectomy in a tertiary care hospital in a developing country. Methods: This was a cross sectional study in which data was retrospectively collected from January 2000 to December 2010. Main outcome measures were maternal morbidity and mortality associated with EPH. Results: The incidence of EPH was 10.52/1000 deliveries. The main causes of EPH were rupture uterus 76 (34.86%), atonic uterus 65 (29.81%), placenta accreta 19 (8.71%), placenta previa 17 (7.7%), and placental abruption 36 (16.5%). Mostly subtotal hysterectomy was the preferred method done in 196 (89.9%) of cases, while total abdominal hysterectomy was done only in 22 (10.09%) of cases. The over all complication rate was 81.2% which included both minor and major complications like hypovolemic shock 180 (82.5%), febrile morbidity 108 (49.5%), wound infection 40 (18.3%), bladder injury 6 (2.75%), and thrombophlebitis 22 (10.09%). The maternal mortality in present review was (10.5%). Conclusion: Frequency of EPH was found to be high in this study. Obstetricians must be skilled in it particularly in developing countries where the main indication of hysterectomy is rupture uterus. Keywords: Emergency peri-partum hysterectomy, maternal morbidity, maternal mortality